2019
DOI: 10.1108/jsocm-12-2017-0088
|View full text |Cite
|
Sign up to set email alerts
|

Utilising stakeholder theory for social marketing process evaluation in a food waste context

Abstract: Purpose Calls for theoretically informed interventions and a more reflexive stance are apparent in social marketing. Moving from a “prove” to “improve” mentality requires evaluations that learn from experience gained to identify improvements to inform future programme success. This paper considers the value of inclusion of stakeholders in process evaluation. Design/methodology/approach Two participant groups (n = 90, n = 182) and one key stakeholder group (n = 22) were surveyed in person, over the phone and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 62 publications
0
28
0
1
Order By: Relevance
“…There are substantial negative environmental externalities attributed to the production of food, and thus, food waste throughout the entire supply chain through to the consumer. The land changes and degradation associated with agricultural practices pose a risk to biodiversity, impact soil erosion and increase pollution of soil and freshwater via the use of chemical fertilisers [3,10]. In Australia, a country prone to drought and water shortages, it is estimated nearly a quarter of all the water used in agriculture is used to produce food that is then lost or wasted [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are substantial negative environmental externalities attributed to the production of food, and thus, food waste throughout the entire supply chain through to the consumer. The land changes and degradation associated with agricultural practices pose a risk to biodiversity, impact soil erosion and increase pollution of soil and freshwater via the use of chemical fertilisers [3,10]. In Australia, a country prone to drought and water shortages, it is estimated nearly a quarter of all the water used in agriculture is used to produce food that is then lost or wasted [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there is an economic argument that improving the efficiency of the food supply chain would make food more affordable at the consumer level for those that lack economic access [2]. Collectively, the environmental and social consequences of the food waste produced throughout the global food system are estimated to have an additional $1.6 trillion impact [10]. This figure is in addition to the estimated direct economic one trillion-dollar cost [10].…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion of multiple stakeholders across the span of a program can improve behaviour change outcomes [20], through enhanced acceptance and adoption of programs into the community [21]. Stakeholder engagement can occur from early formative research and concept development stages [22], through to program implementation and evaluation stages [23, 24]. Freeman [25] defines stakeholders as “any group or individual who can affect or is affected by the achievement of an organization’s objective” (p.53).…”
Section: Introductionmentioning
confidence: 99%
“…Having described various definitions of social marketing and its relationship to commercial marketing and the fact that "there are too many definitions of social marketing being used, and these definitions conflict in major and minor ways" (Andreasen, 2002: 4). Recent studies showed the effectiveness of social marketing interventions at different points in complex dynamic system (Hodgkins et al, 2019;Kassirer et al, 2019;Saunders & Truong, 2019). Whilst social marketing has been continuing to capture increasing research attention in different settings across the globe, local movements and organizations in Kazakhstan are getting more involved in social marketing activities as well.…”
Section: Continuing and Growing Interest In Social Marketingmentioning
confidence: 99%